Sistem Informasi Inventory Gudang Elektronik Berbasis Web - Wau, Kebenaran; Mustika, Wida Prima; Kumalasari, Jefina Tri (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Inventory is a stock of an item or resource, material, material that is stored and fulfills requests from consumers or customers at any time for sale within a period. Many companies in carrying out their activities often experience problems as one example faced is the problem of purchasing, selling and reporting systems that take place within the company, due to the lack of accurate data. At the Sugi Teknik Electronic Store there is a warehouse where sales and purchase data are still manual or not computerized, to check the stock of goods, employees must record incoming and outgoing goods data so that it takes a lot of time in making reports. From the various problems that arise, the authors want to create an Electronic Warehouse Inventory Information System. This application contains recording of incoming and outgoing goods, sales reports, purchase reports, returns or operational reports and income reports making it easier to get information quickly, clearly and accurately.